Analisis Data Mining Menggunakan Metode Algoritma C4.5 Menentukan Penerima Bantuan Langsung Tunai - Lukman Bachtiar; Mahradianur Mahradianur (LPPM Universitas Bina Sarana Informatika, 2023)
Bantuan Langsung Tunai (BLT) adalah bantuan yang dibuat oleh pemerintah untuk orang atau keluarga yang kurang mampu dan rentan akan kemiskinan dengan mereka yang memenuhi persyaratan yang ada pada program. Tujuan peneltian ini untuk memberikan masukkan tentang menentukan apakah keluarga tersebut masih berhak menerima atau tidak berhak menerima bantuan BLT, dimana masih ada keluarga yang berhak menerima dan memenuhi syarat dari program bantuan pemerintahan ini. Sumber data yang diperoleh dapat dari Kantor Desa Regei Lestari. Metode yang dipakai pada penelitian merupakan teknik data mining dengan algoritma C4.5 yang diterapkan pada software RapidMiner. Atribut yang dipakai untuk menentukan keluarga yang berhak menerima dan tidak berhak menerima pada program bantuan BLT yaitu Penghasilan, Status, Pekerjaan, Umur. Direct cash assistance (BLT) is assistance provided by the government for underprivileged and vulnerable people or families with those who meet the requirements of the program. The purpose of this research is to provide input on determining whether the family is still entitled to receive or not entitled to receive BLT assistance, where there are still families who are entitled to receive and meet the requirements of this government assistance program. The source of the data obtained can be from the Regei Lestari Village Office. The method used in this study is a data mining technique with the C4.5 algorithm applied to the RapidMiner software. The attributes used to determine families who are entitled to receive and who are not entitled to receive the BLT assistance program are Income, Status, Occupation, Age. The results of data classification using the C4.5 algorithm method and testing with RapidMiner are If Occupation = farmhand then the result is accepting with a value of 16 items from accepting and 0 not accepting, then the determining factor is obtained who is entitled to receive and who is not entitled to receive assistance direct cash (BLT).